1981
DOI: 10.1007/978-1-349-00784-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Physics

Abstract: The paperback edition of this book is sold subject to the condition that it shall not, byway of trade or otherwise, be lent, resold, hired out, or otherwise circulated without the publisher's prior consent, in any. form of binding or cover other than that in which it is published and without a similar condition including this condition being imposed on the subsequent purchaser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
1
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 0 publications
1
121
1
4
Order By: Relevance
“…The theory of electrical resistivity of metals and alloys has been the subject of a number of reviews and has constituted a large portion of the material in several books [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: 4 Imentioning
confidence: 99%
“…The theory of electrical resistivity of metals and alloys has been the subject of a number of reviews and has constituted a large portion of the material in several books [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: 4 Imentioning
confidence: 99%
“…Since the invocation of the concept of apparently characteristic, material-specific temperature parameters, Θ, within Debye's classical paper [1] on specific heats of solids, one was concerned with a large variety of quotations of corresponding Θ values (so-called "Debye temperatures") within numerous thermophysical research papers, including various representative review articles [2][3][4][5] and books [6][7][8][9][10]. A brief inspection of the enormous Θ data material published hitherto, however, showed readily that it is obviously not possible to find unique Θ values for the individual materials in question, which should apply to duly broad temperature regions.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of numerical fittings of measured (isobaric) heat capacities, ( ), on the basis of (1), it has continually been found that, in contrast with Debye's original suggestion [1], proper simulations of such heat capacity curves can in fact be realized only by admitting rather strong -dependencies of the material-specific Debye temperatures, Θ ( ). This statement applies above all to the liquid-helium-hydrogen 2 Advances in Condensed Matter Physics region, where the adjusted Θ ( ) values are as a rule rapidly falling [3][4][5][12][13][14][15][16][17] from their → 0 limiting levels, Θ (0), to certain minimum values, Θ min , which used to be located in the vicinities of ≈ Θ (0)/15. Furthermore, towards higher temperatures, many Θ ( ) curves show a more or less pronounced increase up to certain material-specific maxima, Θ max , the actual magnitudes of which are in many cases significantly higher than the respective Θ min levels.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that for an uniaxial ferroelectric the free energy of unpolarized crystals is equal to zero [32][33][34] , the free energy, G, of polarized crystals could be written as:…”
Section: Theory Of Ferroelectricitymentioning
confidence: 99%